MELACAK PERAN ELIT NU DALAM PERTEMUAN ISLAM DAN TRADISI LOKAL DI PAMEKASAN - Hasan, Nor (STAIN PAMEKASAN, 2011)
Islam attends not in the centre of culture vacuous society, but attends to find local traditions which expands and goes in the middle of plural society. that Local traditions remain to be defended, come up with next process coloured by Islami values. Among local traditions which still expand in society is âpelet kandung and sarwahâ, representing circular ceremony of life and death.This research leaves from two elementary problems that is; society perception about local tradition and role of NU elite in Islam meeting with local tradition. NU Elite meant in this article is figure â Kiai and Nyai Langgar or Kiai and Nyai Pesantren- owning influence at society, they are merged into NU, either through cultural or structural. Research result indicate that the society comprehends local tradition as a syariat which must be done, in consequence represents bengatoh lalampan ( ancestors sunnah), even if they do not comprehend the synbolic meaning of the tradition. Whereas NU elites (Kiai and Nyai) play its role by the way: first, giving the understanding about tradition meaning to society. second, giving set an example in executing tradition. Third, Preserving the tradition which is still thought well by straightening and changing the tradition assumed digress from Islamic dogma. Method is performed within that tradition change is al muhafadah ala al qodim al shaleh wa al ahdu bi al jadid al ashlah.